MODELING OF SMECTITE ILLITIZATION IN BURIAL DIAGENESIS ENVIRONMENTS - Cuadros J. (My University, 2006)
The kinetics of smectite illitization in shale samples from eight wells have been modeled using the equation -dS/dt = kK0.25S5 [Cuadros, J., Linares J., 1996. Experimental kinetic study of the smectite-to-illite transformation. Geochim. Cosmochim. Acta 60, 439-453], where S is the proportion of smectite layers in illite-smectite (I-S), t is time, k is the rate constant and K is the concentration of potassium. The I-S compositions and the physical parameters were obtained from the literature. Potassium concentration is the only unknown parameter and it was chosen to fit the experimental data. I propose that this variable is termed "effective K concentration," as it is affected not by the actual K concentration alone but also by those of other cations that compete with K for the smectite interlayer sites, especially Ca, by ion mobility in the sediments and possibly by other variables. The kinetic equation allows an accurate fit to the experimental data in all the wells, reproducing both the illitization onset and the patterns of the plots of % smectite vs. depth. The relative changes of the values of "effective K concentration" compare well with K/Ca equivalent ratios in the whole rock. Three of the modeled wells, located in near proximity, produced similar "effective K concentration" patterns. These results support the validity of the equation used in the models. They also suggest that this equation can be used to assess K concentrations in sediments and K mobility within basins.
Keywords: BURIAL DIAGENESIS; ILLITIZATION; NUMERICAL MODEL; REACTION KINETICS; SMECTITE